PENGKLASIFIKASIAN SISWA BERDASARKAN PRESTASI BELAJAR DENGAN MENGGUNAKAN LOGIKA FUZZY CLUSTERING - Pribadi, Feddy Setio (Lembaran Ilmu Kependidikan, 2009)
Analyzing data of students evaluation is often a difficult work for a lecturer.The analysis is aimed to know the students ability in mastering materials so that thelecturer can classify the students based on their ability. This article provides a methodcalled ÃÂ fuzzy clusteringÃÂ which is used for classifying students based on theirachievement. This method is an algorithm that was adopted from human reasoning sothat in determining a decision it is expected to more humane. Fuzzy clusteringÃÂ usesmember function to classify students according to value which shares common characteristics. The experiment revealed that the most optimum result to classify 40students marks comprises 3 groups. The central cluster is 34.7365 (cluster 1),58.1670 for cluster 2, and 85.1248 for cluster 3. The three cluster centers were used tocalculate the students marks which are close to each cluster. With this methodgrouping students based on learning achievement of is more flexible and has a hightolerance value.Kata kunci : logika fuzzy, fuzzy clustering, klasifikasi, dan prestasi belajar